Electric Wire in the Urinary Bladder: Surgical Challenges and Comprehensive Literature Insights - Daniel Porav-Hodade; Raul Gherasim; Ciprian Todea-Moga; Tibor Reman; Bogdan Ovidiu Feciche; Kosza Hunor; Madalin Guliciuc; Mártha Orsolya Katalin Ilona; Ioan Coman; Nicolae Crisan (Diagnostics)
Background/Objectives: An electric wire inserted into the bladder or urethra presents a specific challenge that is frequently encountered in such cases: the potential formation of a tight knot, making extraction nearly impossible. The primary objective of this study was to share our personal experience with patients who had intravesical electric cable insertions and to provide an extensive literature review, offering detailed insights into the various strategies reported for managing such foreign body cases. Methods: Of the four cases with a foreign body in the lower urinary tract, two involved patients aged 19 and 53, respectively, who had inserted an electric cable. During their attempt at self-removal, they developed an intravesical knot, as confirmed by radiographic imaging. Results: In the first case, a bipolar approach was used: a cystoscope was inserted transurethrally into the bladder alongside the cable, while a laparoscopic trocar was introduced suprapubically. Using laparoscopic scissors, the cable was successfully cut and removed. In the second case, due to the cable’s size, a direct cystotomy was performed. At the 3-month follow-up, the uroflowmetry results were normal for both patients. A psychiatric evaluation revealed no abnormalities in the first patient, while the second patient was diagnosed with polyembolokoilamania. Conclusions: The removal of self-inserted electric cables from the urethra and bladder is a challenging procedure, often requiring the urologist’s creativity to prevent potential complications. Many cases can be resolved endoscopically; however, even this minimally invasive approach must be tailored to each case to provide the most suitable solution for the patient.